Distance ditermination by laser triangulation method - 362175 Mohd. Noor Shafaruddin Apandi; Yusof Munajat, supervisor; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2007